Hubungan dukungan sosial dengan self esteem pada remaja pengguna game online - Nafishah Dwi Lestari; Nawang Warsi Wulandari; Agustin Rahmawati (University of Merdeka Malang, 2021)
In this modern era, everything can be accessed by the internet. One of them is internet based game. This development is very appealing to the attention of the community, one of is adolescent consumers. Many adolescent are looking for fun and appreciation from online games. Adolescents at the age of 13-22 years are vulnerable to seeking social support because of the transition period. Loneliness and low attention from the environment resulting on low self-esteem in adolescents. Quantitative research was conducted to study the relationship of social support and self-esteem in adolescents. This study uses an infinite population, which is an online adolescent user game in Malang. The sampling technique used was accidental sampling on total 100 adolescent. Measuring instruments in the form of a scale of social support and self-esteem. Significance test results of 0,000 and hypothesis test results of 0.760. It means that there is positive correlation between social support and self esteem. Positive correlation means that higher social support, resulting on higher self-esteem, vice versa the lower the social support resulting on the lower self-esteem.